Jacarapé em ruínas: o conflito socioambiental causado pelo polo turístico Cabo Branco em João Pessoa - Portioli, July (2025)
The socio-environmental conflicts arising from the implementation of tourism megaprojects on the Brazilian coast reveal a historical process of territorial expropriation that has resulted in state violence, environmental degradation, and inequality in the use and occupation of spaces. This dissertation investigates the socio-environmental conflict generated by the implementation of the Cabo Branco Tourist Complex megaproject on the coast of Paraíba, analyzing it as a contemporary manifestation of this historical process. It argues that such processes, inherent to the logic of capitalist development, are intensified by the actions of the neoliberal state, which operates as a facilitator of capital's expansion into territories and communities. The study deepens this analysis by incorporating the framework of the Coloniality of Power, demonstrating how colonial hierarchies are rearticulated to legitimize territorial dispossession. The central methodology used was militant research, guided by transformative praxis. This epistemological and political approach sought not only to analyze the conflict but also to give visibility and amplify the voices of subalternized subjects. Data collection involved qualitative research using semi-structured interviews with community members and stakeholders, as well as documentary research using primary and secondary sources. The results reveal the intricate interplay between the state and capital in the reproduction of territorial exclusion and rights violations, while also highlighting community resistance and the importance of engagement in expanding citizenship and socio-environmental justice.